OPTICAL FIBRES : Quasi-single-mode hybrid fibre with anomalous dispersion in the 1 μm range. (31st August 2016) - Aleshkina, S S; Yashkov, M V; Senatorov, A K; Iskhakova, L D; Bubnov, M M; Gur'yanov, A N; Likhachev, M E
Abstract: We have proposed and demonstrated an approach for ensuring quasi-single-mode operation of a cylindrically symmetric hybrid fibre having anomalous dispersion at wavelengths around 1 μm. Basic to this approach are distinctions between spatial fibre mode distributions and the use of a high-loss ring layer in the region of a minimum in the electric field of the operating hybrid mode.